Immune Status of Pancreatic Cancer Patients Receiving Cryosurgery - Vladimir M. Zemskov; Konstantin N. Pronko; Dmitrii A. Ionkin; Alexei V. Chzhao; Maria N. Kozlova; Alexander A. Barsukov; Nadezhda S. Shishkina; Valentina S. Demidova; Andrei M. Zemskov; Amiran Sh. Revishvili (Medical Sciences, 2019)
Cryosurgery used on patients with unresectable pancreatic cancer improved their quality of life, but mainly because of the pain relief. In postoperative patients, multifaceted changes in immunity were found, and the state of the immune system prior to surgery often was a decisive factor to indicate whether further disorders in the postoperative period would develop, or by contrast, it would boost its recovery. Some patients receiving cryosurgery showed immune system imbalance and activation, and of antitumor immunity in particular. It has been suggested that the advisability of immunotropic therapy for specific treatment algorithms should be predicted or the therapy should be suspended at some pathologic stage, and this has been immunologically confirmed. Cryosurgery should be considered as a reasonable alternative to the existing types of surgery for pancreatic cancer or as an essential component of multimodal therapy, consisting of topical cryosurgery, chemotherapy, and immunotropic therapy, to boost antitumor immunity and to discontinue cytoreductive therapy due to its toxic effects.